Thinking contemporary curating - Smith, Terry (New York : Independent Curators International, 2012)
The lure -- What is contemporary curatorial thought? -- Shifting the exhibitionary complex -- Artists as curators/Curators as artists -- Curating contemporaneity -- Curatorial practice now -- The infrastructural.
CCS Gent
boek